Understanding perceptions on 'Buruli' in northwestern Uganda: A biosocial investigation. - Georgina Pearson (Public Library of Science (PLoS), 2018)
BACKGROUND:An understudied disease, little research thus far has explored responses to Buruli ulcer and quests for therapy from biosocial perspective, despite reports that people seek biomedical treatment too late. METHODS AND FINDINGS:Taking an inductive approach and drawing on long-term ethnographic fieldwork in 2013-14, this article presents perspectives on this affliction of people living and working along the River Nile in northwest Uganda. Little is known biomedically about its presence, yet 'Buruli', as it is known locally, was and is a significant affliction in this region. Establishing a biosocial history of 'Buruli', largely obscured from biomedical perspectives, offers explanations for contemporary understandings, perceptions and practices. CONCLUSIONS/SIGNIFICANCE:We must move beyond over-simplifying and problematising 'late presentation for treatment' in public health, rather, develop biosocial approaches to understanding quests for therapy that take into account historical and contemporary contexts of health, healing and illness. Seeking to understand the context in which healthcare decisions are made, a biosocial approach enables greater depth and breadth of insight into the complexities of global and local public health priorities such as Buruli ulcer.